The narrative program in the novel God (Journal of the College of Basic Education, 2022)
The novel “These People” by Majid Tobia is considered one of the novels symbolically expressing the nature of the state in the countries of the Arab world, and immersing it in coding, as well as generalizing the model expressed in it. (aibot) to express the name of the country concerned. This novel can be considered a kind of satirical irony or black political comedy, and it remained immune to an analysis that reveals the nature in which events are organized in a specific narrative program. Our research intends, here, to reveal a completely specific goal; It is the narrative program in this novel, benefiting from the narrative semiotics presented by the Paris Semiotic School. The research will focus on analyzing the narrative level among the three levels in the semiotic analysis.